The Exchange Rate of Iraqi Dinar between De facto Regime and De jure Regime in the Iraq during (2004-2012) - داغر, محمود محمد; مهوس, حسين عطوان (Journal of Economics and Administrative Sciences, 2018)
The understanding exchange rate policy is fundamental in order to identify the mechanism by which works out macroeconomic, And the vital for macroeconomic analysis and empirical work to differentiate between the de facto regimes and de jure regimes, Where the proved surveys and studies issued by the international monetary fund that there is divergence between the de facto regime (Regime of exchange applied by the country actually) and between the de jure regime (Regime de jure through the documents and formal writings of officials of the central bank), And launched studies on the de facto regime (Being a the basis of evaluating monetary policy) Stabilized (peg-like)arrangements or Crawl-like arrangements.        So a monetary policy in Iraq after the central bank to get of independence in 2004 a major transformation, But in the under the financial system lacks the monetizing  and financial depth and the rise in bank liquidity be a normal channels to transfer the impact of monetary policy is ineffective, Thus, The main tool available to the central bank of Iraq are the exchange rate, It adopted a latter exchange rate nominal anchor for monetary policy, Thus, The levels of intervention via open market operations (Currency Auctions) in Iraq,  Are the reflecting de facto regime and not de jure regime, Meaning that divergence between the de facto regimes and de jure regimes, Where that rentier Iraqi economy and the weakness of flexible productive his device, As well as the expansion of government expenditure In his part operational at the expense investment, All this handicap in price stability, And therefore impose a constraint on the monetary authority to defend the exchange rate of the dinar in the hope of achieving price stability